2020
DOI: 10.1002/nafm.10456
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Infection in Hatchery‐Origin Chinook Salmon Correlates with Abundance of Ceratonova shasta Spores: Implications for Management and Disease Risk

Abstract: Ceratonova shasta is an endemic myxozoan parasite that impacts salmonid populations in the Klamath River (USA). High densities of C. shasta actinospores negatively affect the survival of migrating juvenile salmonids. Each year, approximately five million fall‐run Chinook Salmon Oncorhynchus tshawytscha smolts are released from a hatchery that is located below Iron Gate Dam, and they travel through an infectious zone where the densities of C. shasta spores are elevated and when disease risk is often highest. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In addition, in the NE Pacific, salmon enhancement hatcheries subsidize natural salmon populations, and since 1950, 3.7 billion Chinook salmon have been released into the Salish Sea from hatcheries in the United States and British Columbia (BC) ( 43 ). The risk posed from emerging infectious disease associated with hatchery fish varies ( 13 , 44 , 45 ) and is largely unknown with respect to PRV-1.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the NE Pacific, salmon enhancement hatcheries subsidize natural salmon populations, and since 1950, 3.7 billion Chinook salmon have been released into the Salish Sea from hatcheries in the United States and British Columbia (BC) ( 43 ). The risk posed from emerging infectious disease associated with hatchery fish varies ( 13 , 44 , 45 ) and is largely unknown with respect to PRV-1.…”
Section: Introductionmentioning
confidence: 99%
“…Study area.-The study area was comprised of three sites on the Klamath River below Iron Gate Dam, the upstream barrier for anadromous salmonids in the Klamath River, in a portion of the river commonly referred to as the C. shasta "infectious zone" (Hallett and Bartholomew 2006;Robinson et al 2020). These sites were selected because they contain habitat conditions representative of the infectious zone, including areas ranging from never inhabiting annelids to those known to consistently host annelids.…”
Section: Methodsmentioning
confidence: 99%
“…Further, an epidemiological model describing how C. shasta dynamics respond to future climate scenarios found that high winter discharge had the greatest impact on lowering the number of infected juvenile fish ( Ray et al, 2015 ), and a statistical model for annelid habitat suitability related hydraulic and substrate variables to annelid host distribution in the Klamath River ( Alexander et al, 2016 ). Other analyses have found a correlative relationship between the prevalence of infection of hatchery-released smolts and the spring peak of spore densities the following year ( Robinson et al, 2020 ), suggesting seasonal links contributing to spore density. This suite of mechanistic and statistical models provides the groundwork to inform simulations of C. shasta during the outmigration period.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, approximately five million Chinook Salmon smolts are released from Iron Gate Hatchery (located below Iron Gate Dam, Fig. 1 ) each year between mid-May and early-June, a period that frequently coincides with peak C. shasta densities ( Robinson et al, 2020 ), exposing hatchery-origin fish to potentially high mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation